Effects of degree of particle agglomeration on the dielectric properties of BaTiO3/epoxy composites - Han, J.-W.; Kim, B.-K.; Je, H.-J. (2008)
BaTiO3/epoxy composites can be applied as the dielectric materials for embedded capacitors. The effects of the degree of BaTiO3 particle agglomeration on the dielectric properties of BaTiO3/epoxy composites were investigated in the present study. The degree of particle agglomeration was controlled by the milling of the agglomerated particles. The size and content of the agglomerated BaTiO3 particles decreased with an increase in the milling time. The dielectric constants and polarizations of BaTiO3/epoxy composites abruptly decreased with the increase of the milling time. It was concluded that the dielectric constants and polarizations of BaTiO3/epoxy composites decreased as the degree of particle agglomeration decreased. The degree of agglomeration of BaTiO3 particles turned out to be a very influential factor on the dielectric properties of BaTiO3/epoxy composites.
Keywords: Agglomeration; Capacitance; Capacitors; Ceramic capacitors; Dielectric devices; Dielectric properties; Dielectric waveguides; Electric equipment; Epoxy resins; Milling (machining); Permittivity; Polarization; Agglomerated particles; BaTiO3/epoxy composites; Degree of agglomerations; Dielectric constant; Dielectric constants; Embedded capacitors; Epoxy composites; Influential factors; Milling times; Particle agglomerations; Dielectric materials